Big Data’s Impact on Jordan Banks’ Organizational Innovation: Examining the Moderating Effects of Management Commitment and Mediating Knowledge Sharing - Mohammad, Sami; Çelebi , Ayşem; Amer, Alrmah Saied R. (International Review of Management and Marketing, 2026)
This research comprehensively examines the impact of big data integration on organizational innovation in the context of Jordanian banks. It builds on prior research to explore the role of “Big Data’s volume, velocity, variety and veracity.” Organizational Innovation and Leadership Besides managerial commitment and knowledge sharing, organizational innovation and leadership are also crucial. The constructs have a proven validity and reliability for at least preliminary validation analysis. A major result of Big Data is a significant effect of volume, velocity and variety on organizational innovations. Further, in reinforcing the need for knowledge sharing as an important mediator of decision-making and problem solving, the study also emphasises the importance of management's support to facilitate this means of communication process with innovative outcomes within a particular organization. The paper suggests for better insight of the importance of data analysis in institutional innovation to cope with external environmental concerns.